2023
DOI: 10.1108/jfra-04-2023-0177
|View full text |Cite
|
Sign up to set email alerts
|

Integrating forensic accounting in education and practices to detect and prevent fraud and misstatement: case study of Jordanian public sector

Esraa Esam Alharasis,
Hossam Haddad,
Mohammad Alhadab
et al.

Abstract: Purpose This study aims to examine the degree of consciousness of forensic accounting (FA) in Jordan. This study surveys practitioners and academicians about their views and thoughts toward the expected role of using FA techniques to detecting and preventing fraud practices and shedding more light on advantages and obstacles of using the FA techniques. Design/methodology/approach To collect the data, a questionnaire was constructed and distributed to the study population which consists of accounting academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Ethical considerations are particularly crucial in cases where digital techniques involve vast amounts of personal and sensitive data. In conclusion, case studies and examples provide valuable insights into the application of forensic accounting and fraud detection techniques in the digital age (Alharasis et al,2023). Real-world instances of successful fraud detection underscore the importance of crossdisciplinary collaboration, continuous monitoring, adaptation to evolving technologies, and adherence to ethical standards.…”
Section: Case Studies and Examplesmentioning
confidence: 97%
“…Ethical considerations are particularly crucial in cases where digital techniques involve vast amounts of personal and sensitive data. In conclusion, case studies and examples provide valuable insights into the application of forensic accounting and fraud detection techniques in the digital age (Alharasis et al,2023). Real-world instances of successful fraud detection underscore the importance of crossdisciplinary collaboration, continuous monitoring, adaptation to evolving technologies, and adherence to ethical standards.…”
Section: Case Studies and Examplesmentioning
confidence: 97%
“…They may also engage in criminal investigations on behalf of the police force and an understanding of legal issues related to business activities (Owojori & Asaolu, 2009;Alharasis et al, 2023)…”
Section: 3the Role Of Forensic Accountingmentioning
confidence: 99%
“…The role of forensic accountants in detecting and investigating fraud and corruption cases has become increasingly crucial in recent years. Forensic accountants use their specialized knowledge of accounting, auditing, and investigation techniques to identify fraudulent activities, investigate them, and provide evidence for legal proceedings (Enofe, Utomwen and Danjuma, 2015;Alharasis et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Research on KAM has primarily examined factors affecting the amount of reported cases (Pinto and Morais, 2019; Sierra-García et al , 2019; Alharasis et al , 2023d, 2023e) and the expanded auditor reporting legal implications of Kachelmeier et al (2020), Gimbar et al (2016) and Asbahr and Ruhnke (2019). The quality of financial reports and the audit procedure during the COVID-19 outbreak were studied as KAM determinants.…”
Section: Introductionmentioning
confidence: 99%